2015
DOI: 10.1177/0145721715601736
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Diabetes Prevention and Control Programs and Policies in Local Health Departments

Abstract: Purpose The purpose of this study is to: (1) assess implementation of evidence-based programs and policies (EBPPs) related to diabetes prevention and control in local health departments; (2) assess feasibility of non-implemented diabetes prevention and control EBPPs; and (3) examine individual- and organizational-level factors associated with implementation of diabetes prevention and control EBPPs. Methods An online survey was administered in January 2015 to key representatives of all local health department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…PHAB lists the Guide as an evidence-based resource ( 9 ). Studies have found that accreditation is related to use of more EBIs in LHDs ( 29 ) and use of evidence in SHDs ( 30 ). In a study by Cilenti et al, LHD participants interviewed reported that accreditation helped to promote use of evidence-based practices, because it required implementing approaches that resulted in desired outcomes ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…PHAB lists the Guide as an evidence-based resource ( 9 ). Studies have found that accreditation is related to use of more EBIs in LHDs ( 29 ) and use of evidence in SHDs ( 30 ). In a study by Cilenti et al, LHD participants interviewed reported that accreditation helped to promote use of evidence-based practices, because it required implementing approaches that resulted in desired outcomes ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 – 13 A quantitative study of LHDs in Missouri assessed the use of 20 diabetes-related EBPPs, feasibility of EBPPs, and personal/organizational barriers to evidence-based practice and found LHDs have an important role in implementing EBPPs. 14 Findings indicate that more widespread adoption of EBPPs would be enhanced by increased education about and encouragement of evidence-based decision making (EBDM). EBDM involves making decisions based on the best available scientific or rigorous program evaluation evidence, applying program planning and quality improvement frameworks, engaging the community in assessment and decision making, adapting and implementing EBPPs for specific populations or settings, and conducting sound evaluation.…”
mentioning
confidence: 99%
“…A pilot study of LHDs in Missouri found organizational characteristics such as LHD size and accreditation status were positively associated with delivering EBIs. 39 While this cross-sectional study does not allow for assessment of causation, it is notable that, at the LHD level, there was a positive association between diabetes prevalence in the state and offering several of the EBIs. This suggests that higher diabetes prevalence may elevate the issue of diabetes as a priority, and LHDs and their partners may respond with additional EBIs; alternately, higher diabetes prevalence may lead to more funding from the Centers for Disease Control and Prevention.…”
Section: Discussionmentioning
confidence: 93%
“…For example, a pilot study in Missouri LHDs found delivering EBIs to be associated with the perception that the agency gives incentives and rewards to help employees use EBDM principles. 39 There is a growing literature that capacity for EBDM can be built with sustained efforts (eg, training, technical assistance). 40 …”
Section: Discussionmentioning
confidence: 99%